2001
DOI: 10.1136/bmj.323.7319.970
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of structured personal care of type 2 diabetes mellitus

Abstract: Objective To assess the effect of a multifaceted intervention directed at general practitioners on six year mortality, morbidity, and risk factors of patients with newly diagnosed type 2 diabetes.Design Pragmatic, open, controlled trial with randomisation of practices to structured personal care or routine care; analysis after 6 years. Setting 311 Danish practices with 474 general practitioners (243 in intervention group and 231 in comparison group). Participants 874 (90.1%) of 970 patients aged >40 years who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
270
2
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(289 citation statements)
references
References 26 publications
(33 reference statements)
9
270
2
8
Order By: Relevance
“…Planned care, as originally advocated by Wagner et al (1), involves redesigning the health care delivery system to support patient self-management by using clinical information and decision support systems (10). Consistent with others, we found that implementation of planned care in a primary care setting was associated with improved performance measures (11)(12)(13)(14) and improved metabolic outcomes (13). Few models of care, including planned care, can consistently improve performance measures when more than five preventive measures (as with diabetes) are targeted (12).…”
Section: Conclusion -The Mayo Healthsupporting
confidence: 82%
See 2 more Smart Citations
“…Planned care, as originally advocated by Wagner et al (1), involves redesigning the health care delivery system to support patient self-management by using clinical information and decision support systems (10). Consistent with others, we found that implementation of planned care in a primary care setting was associated with improved performance measures (11)(12)(13)(14) and improved metabolic outcomes (13). Few models of care, including planned care, can consistently improve performance measures when more than five preventive measures (as with diabetes) are targeted (12).…”
Section: Conclusion -The Mayo Healthsupporting
confidence: 82%
“…For instance, a 10% increase in immunizations (similar to the change from 64 to 80% associated with DEMS use in this study) could mean, in a population of 1,000 patients with diabetes followed for 1 year, two fewer deaths and one fewer hospitalization due to pneumonia (15). The expanded role of the diabetes nurse educator in this project provides an example of the role played by members of the health care team in quality improvement activities (3,(11)(12)(13). All members of the team actively participated in the adoption of guidelines and assisted in the planning of multifaceted interventions.…”
Section: Conclusion -The Mayo Healthmentioning
confidence: 80%
See 1 more Smart Citation
“…Vi inkluderte syv randomiserte, kontrollerte studier publisert mellom 2001 og 2011 (tab 1) (13 -19 (19). Antall pasienter varierte fra 335 til 7 412, og gjennomsnittsalderen var rundt 60 år.…”
Section: Resultaterunclassified
“…24 This study included clinically diagnosed patients with type 2 diabetes. GPs were assigned to routine care or structured care.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%